Automated diagnosis of colon cancer using hyperspectral sensing. Issue 3 (26th February 2018) - Beaulieu, Robert J.; Goldstein, Seth D.; Singh, Jasvinder; Safar, Bashar; Banerjee, Amit; Ahuja, Nita
Abstract: Background: Surgical management of colorectal cancer relies on accurate identification of tumor and possible metastatic disease. Hyperspectral (HS) sensing is a passive, non‐ionizing diagnostic method that has been considered for multiple tumor types. The ability to use HS for identification of tumor specimens during surgical resection of colorectal cancers was explored. Methods: Patients with colorectal cancer who underwent operative resection were enrolled. HS measurements were performed both intra‐ and extra‐luminally. Spectral results were correlated with pathologic evaluation. Results: Fifteen patient specimens were analyzed. For patients with confirmed colorectal cancer, extraluminal spectra analysis yielded 61.68% sensitivity with 90% specificity. For intraluminal specimens, sensitivity increased to 91.97% with 90% specificity. Conclusions: Hyperspectral sensing can reliably detect tumors in resected colon specimens. This research offers promising results for a diagnostic technology that is non‐ionizing and does not require the use of contrast agents to achieve accurate colorectal cancer detection.